Strong CO(2 )adsorption in narrow-pore ADOR zeolites: A combined experimental and computational study on IPC-12 and related structures - Trachta, Michal; Volny, Tomas; Bulánek, Roman; Pozdílková, Eva; Halamek, Jakub; Rubeš, Miroslav; Shamzhy, Mariya; Mazur, Michal; Cejka, Jiri; Bludsky, Ota (Elsevier, 2023)
The ADOR method of synthesizing new zeolites has yielded a range of innovative siliceous materials featuring narrow pores, which facilitate relatively strong CO2 binding. This combined experimental and computational study investigates the adsorption properties of known ADOR materials (isoreticular zeolites of the UTL family and zeolites synthesized from UOV, *CTH, IWR, and IWW parent materials), as well as hypothetical ADOR zeolites derived from UOV, IWR, and IWW. The adsorption heat of carbon dioxide on the investigated ADOR materials was ascertained through i) a series of isotherms measured at 278-318 K and ii) Monte Carlo simulations at 300 K utilizing the DFT/CC technique. Consistently higher heats of CO2 adsorption found in -D4R materials (double four-membered ring interlayer linker removed from a parent zeolite) indicate stronger dispersion interactions compared to their -S4R counterparts (single four-membered ring removed). Among ADOR zeolites, IPC-12 (UOV-D4R) was identified as a zeolite possessing the strongest CO2 binding (heat of adsorption at the zero-coverage limit of 37.3 and 37.9 kJ/mol, as determined by experiment and theory, respectively). This high adsorption energy can be attributed to a distinct structural pattern featuring an elongated shape, which effectively accommodates CO2. Comparable structural patterns to IPC-12 were also detected in as-yet hypothetical ADOR products (IWR-D4R and IWW-D4R).
Silná adsorpce CO(2) v zeolitech ADOR s úzkými póry: Kombinovaná experimentální a výpočetní studie IPC-12 a příbuzných struktur
Keywords: ADOR; Zeolites; Adsorption; Carbon dioxide; Ab initio modeling; Metropolis Monte Carlo; Importance sampling; ADOR; zeolit; adsorpce; CO2; ab initio modelování